Faktor Kesuksesan Akselerasi Ekspor UKM Industri Halal di Indonesia: Analisis Delphi - Yudi Ahmad Faisal; Ardi Apriliadi (LPMP Imperium, 2021)
This study aims to design the success factors for the export acceleration of Halal Industry SMEs in Indonesia. The model developed combines secondary data processing (literature review on the success factors for the export acceleration of Halal Industry SMEs) and primary data (Focus Group Discussion). The method used in this research is the Delphi method. The Focus Group Discussion (FGD) was conducted by selecting purposively (based on specific considerations) discussion lighters and expert resource persons (expert panel) totaling 26 expert respondents who came from export practitioners, government representatives, academics, and export SME associations and were considered to have experience and knowledge related to the export of Halal Industry SMEs. The FGD produced 14 indicators from the first variable, nine from the second variable, six from the third variable, and four from the fourth variable. Third, 33 indicators from these four variables were then used as material for preparing a questionnaire to be submitted back to expert respondents to justify and assess the importance of each of these indicators using a Likert scale of 1-5..